Free education as superstructure: Phenomenological study of free private education - Marhaeni Mega Wijayanti; Tuti Budirahayu; Novri Susan (Masyarakat, Kebudayaan dan Politik, 2019)
As a manifestation of functionalism, free education becomes a way to eradicate economic disparity by opening access to school for all people. This method is standard in many developing countries as it could foster development. However, the most fundamental problem of this disparity, oppression, and class domination are understudied. To make things worse, studies that do discuss these topics suffer from class bias conceptualization of free education. Therefore, this study aims to demonstrate how free education takes part in a capitalistic society as a superstructure through the correspondence thesis. Subsequently, this study identifies essential elements in (capitalistic) free education. Phenomenological-based qualitative method is used to describe experiences of 21 informants in Selamat Pagi Indonesia (SPI) Senior High School. Data gathered from observation, interview, and secondary sources, and then analyzed phenomenologically. We found that free education, instead of bringing people to equality and freedom from disparity, entraps students deep into modern capitalism through 1) normalization to serve, and 2) giving up power to the capitalist. This condition would benefit many corporations from taking part in aiding the school foundation and perpetuate the domination of the bourgeoisie over the working class. Thus, this study suggests that the capitalistic feature of free education is disrupting its conventional conceptualization.